MATLAB Modeling of Component in Electrical Discharge Machining (EDM) Pulses - Betantya Nugroho; Yahya, Azli; Mat Sidek, Abd. Rahim; Andromeda, Trias (Media Journal of General Computer Science, 2024)
Electrical Discharge Machining (EDM), is a machining technique for working with conductive materials. During the EDM process, electrical discharge energy is transformed into thermal energy, leading to the erosion of the workpiece. The energy utilized by the EDM process is represented by the time-dependent current, which determines the energy density employed for workpiece erosion. Ideally, during a discharge event, the current pulse should exhibit a square wave shape. However, in practice, EDM circuits often incorporate parasitic components that lead to non-square waveforms or transient currents. In this paper, we describe the simulation of parasitic components using MATLAB, revealing that these components alter the signal waveform and affect the achievement of a square pulse wave in MRR. The presence of parasitic components results in transient current patterns during the discharge phase and, consequently, a reduction in MRR. The implementation of a square wave current, however, enhances the MRR value and increases the efficiency of the EDM process